Stuck in a rut: Potential costs of sand roads to gopher tortoises Gopherus polyphemus - Gilson, L.; Bateman, Bill (Oxford University Press, 2015)
Roads affect wildlife significantly through direct mortality but also through behavioral change. We explored the effects of unsurfaced sand roads with a low traffic volume on the travelling behavior of gopher tortoises Gopherus polyphemus in scrub habitat in central Florida, as evidenced by the tracks left by tortoises on sand roads. Tortoises (and most other taxa leaving tracks on the roads) did not appear to make use of roads for travel but attempted to cross them, the success of which was influenced by the size of the individual. Smaller animals (presumably younger tortoises) were more challenged than larger animals by both sand road widths and depths of vehicle ruts in sand roads. Sand roads may present both physical and physiological challenges to gopher tortoises, particularly to small ones. This research provides further evidence that the negative influence of roads in fragmenting the environment is not limited to vehicle mortality.